2022
DOI: 10.3390/su14106192
|View full text |Cite
|
Sign up to set email alerts
|

Blockchain Technology in Operations & Supply Chain Management: A Content Analysis

Abstract: Scholars are increasingly examining how the distributed blockchain technology can counter specific supply chain and operations management challenges. Various research approaches emerge from different scholarly backgrounds, but the interrelation of research areas and current trends has not been adequately considered in a systematic review. We employ a data-driven content analysis approach to examine previous research on blockchain technology in operations management and supply chain management. We investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 310 publications
1
21
0
1
Order By: Relevance
“…Additionally, RBV suggests that firms should focus on building and acquiring the resources and capabilities necessary to implement blockchain effectively, such as IT infrastructure, data analytics tools and personnel with expertise in blockchain development and implementation (Tseng et al, 2023). Principal-agent theory (PAT) is also relevant to the O&G SC, as it highlights the importance of designing incentive structures and monitoring mechanisms that align the interests of stakeholders in the blockchain ecosystem (Lohmer et al, 2022). For instance, O&G companies may need to design incentive structures that encourage suppliers and other stakeholders to provide accurate and timely data and may need to implement monitoring mechanisms to ensure that data is accurate and not subject to tampering or fraud.…”
Section: Literature Review 21 Digital Transformation Phenomenon and U...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, RBV suggests that firms should focus on building and acquiring the resources and capabilities necessary to implement blockchain effectively, such as IT infrastructure, data analytics tools and personnel with expertise in blockchain development and implementation (Tseng et al, 2023). Principal-agent theory (PAT) is also relevant to the O&G SC, as it highlights the importance of designing incentive structures and monitoring mechanisms that align the interests of stakeholders in the blockchain ecosystem (Lohmer et al, 2022). For instance, O&G companies may need to design incentive structures that encourage suppliers and other stakeholders to provide accurate and timely data and may need to implement monitoring mechanisms to ensure that data is accurate and not subject to tampering or fraud.…”
Section: Literature Review 21 Digital Transformation Phenomenon and U...mentioning
confidence: 99%
“…Additionally, RBV suggests that firms should focus on building and acquiring the resources and capabilities necessary to implement blockchain effectively, such as IT infrastructure, data analytics tools and personnel with expertise in blockchain development and implementation (Tseng et al ., 2023). Principal-agent theory (PAT) is also relevant to the O&G SC, as it highlights the importance of designing incentive structures and monitoring mechanisms that align the interests of stakeholders in the blockchain ecosystem (Lohmer et al. , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…On the other hand, IIoT contributes to increasing reliability in the production process through precise control over product quality (Boyes et al ., 2018). This technology can be used to detect fraud or theft by using RFID technology (Lohmer et al ., 2022). Concerning inventory control, considerable research in the literature has shown the importance of using IIoT and RFID in improving inventory control, contributing to reducing inventory-related costs (Mashayekhy et al ., 2022; Peter et al ., 2023).…”
Section: Theoretical Framework and Hypotheses Formulationmentioning
confidence: 99%
“…The recognition of the importance of emerging technologies in supporting performance in the supply chain is shown in the literature (Al-Khatib and Ramayah, 2023;Rajab et al, 2020;Ventura et al, 2023). Current recent studies have emphasized the importance of emerging technologies in improving efficiency, providing technological contributions and advanced analytical capabilities that transform the traditional supply chain form into a digital and smart form (Lohmer et al, 2022), providing several benefits at the level of the supply chain and the firms' organizational level.…”
Section: The Indirect Effect Of Scvmentioning
confidence: 99%
“…By providing transparency, automation, and decentralized verification, blockchain empowers experts and stakeholders to verify sustainability claims, enforce ethical standards, and promote responsible supply chain practices. The integration of expertise as an intermediary in blockchain-driven supply chain management can contribute to building trust, improving accountability, and driving future sustainable management practices [ [83] , [84] , [85] ].…”
Section: Introductionmentioning
confidence: 99%